Деякі зауваги щодо української виразні в царині транспорту та шляхів - Джура, Марія; Нікіпчук, Сергій (Видавництво Національного університету "Львівська політехніка", 2007)
Йдеться про філософське обґрунтування необхідности витвору наукової термінології мовними засобами рідної мови та про шкідливість запозичень. Запропоновано деякі практичні поради щодо витвору термінів. Подано терміни, що існували раніше, та ті, що використовують сьогодні, а також запропоновано нові вирази в царині транспорту та шляхів. The authors of the article treat the issue of the philosophical background for creating scientific terminology on the basis of the Ukrainian language as well as that of the linguistic damage caused by borrowings. Some practical pieces of advice concerning the creation of terms are suggested. Some terms which were used in the past along with those used nowadays, as well as new terms in the field of transport and roads created by the authors of the article are given in it.